Tree roots and damages in the Jewish catacombs of Villa Torlonia (Roma) - Caneva, G.; Galotta, G.; Cancellieri, L.; Savo, V. (Journal of Cultural Heritage, 2009)
Damages to hypogeal archaeological monuments, caused by the growth of tree roots, are frequently reported in the city of Rome. Problems of compatibility between trees and underground structures may become complex in the case of historical gardens. The Jewish catacombs of Villa Torlonia show relevant conservation problems, some of them arising from damages due to root growth, and consolidating interventions seem to be urgent. Some species in the gardens, especially Ficus carica L., but also Quercus ilex L. and Pinus pinea L., have developed a strong root system, growing for many meters in lateral distance and for some meters vertically. The plants responsible for the various alterations were identiﬁed by their wood anatomy and a methodology to treat similar problems has been proposed. Data collected aim to avoid errors made in managing the plant cover of an archaeological site.
The following values have no corresponding Zotero field: publisher: Elsevier Masson SAS
Keywords: archaeological site; catacombs; hypogeal conservation; rome; tree roots and buildings; Trees; wood anatomy

Tree roots and damages in the Jewish catacombs of Villa Torlonia (Roma) - Caneva, G; Galotta, G; Cancellieri, L; Savo, V (Journal of Cultural Heritage, 2009)
Damages to hypogeal archaeological monuments, caused by the growth of tree roots, are frequently reported in the city of Rome. Problems of compatibility between trees and underground structures may become complex in the case of historical gardens. The Jewish catacombs of Villa Torlonia show relevant conservation problems, some of them arising from damages due to root growth, and consolidating interventions seem to be urgent. Some species in the gardens, especially Ficus carica L., but also Quercus ilex L. and Pinus pinea L., have developed a strong root system, growing for many meters in lateral distance and for some meters vertically. The plants responsible for the various alterations were identiﬁed by their wood anatomy and a methodology to treat similar problems has been proposed. Data collected aim to avoid errors made in managing the plant cover of an archaeological site.
Keywords: archaeological site; catacombs; hypogeal conservation; rome; tree roots and buildings; Trees; wood anatomy

Long-term monitoring of metal pollution by urban trees - Gratani, Loretta; Crescente, Maria Fiore; Varone, Laura (Atmospheric Environment, 2008)
The atmospheric pollution level in Rome was monitored in the year 2006. Five sites in the historical centre were considered. The concentration of Al, Fe, Cu, Zn, and Pb was analysed in washed and unwashed Quercus ilex leaf samples. Moreover, in order to verify the changes in atmospheric pollution in the historical centre of the city after the introduction of the limited trafﬁc zone (LTZ), previous data collected in the years 1979 and 1996 were also considered. The leaf’s internal concentration of Al, Fe, Cu, Zn, and Pb was 28, 22, 40, 77 and 37%, respectively, of the total concentration, and it was in the same range monitored in the years 1979 and 1996. The results underlined a signiﬁcant (p < 0.05) decreasing of metal concentration on unwashed leaves with on an average 92%, compared to ones monitored in the year 1979. The mean value of the total trafﬁc ﬂow during the limitated period (Monday to Friday, from 6:30 a.m. to 6:00 p.m, and Saturday from 2:00 to 6:00 p.m.) was 75.000 vehicles, compared to 90.000 ones before the electronic gates were activated; moreover, a 15% decrease in the daily trafﬁc peak (8:30–9:30 a.m) was monitored. The metal concentration in Q. ilex leaves was be related to motor vehicle emissions, conﬁrmed also by PCA. The data obtained on the leaf metal concentration trend in Rome, over a period of 27 years, underlined the importance of the City Council provisions. These results conﬁrmed the use of Q. ilex for long-term monitoring of metal concentration in those urban areas where the species was naturally present, and widely distributed in the landscape.
Keywords: Bio-monitor; Metal pollution; Quercus ilex; rome; Vehicular trafﬁc